Análise dinâmica não linear da interação solo-estrutura em plataformas marítimas - Coutinho, Alvaro Luiz Gayoso de Azeredo (1984)
This work deals with the dynamic nonlinear analysis of soil-structure interaction in offshore platforms, during its installation and operation. Hence, it was developed a numerical model to allow the representation of the soil fundamental plastic and rheological properties. This model also enhances the utilization of complete constitutive relations for soil. Several applications in structural dynamics and wave propagation problems were studied. They were solved by an implicit incremental-iterative formulation for the nonlinear movement equations. Finally, some conclusions regarding the performance of the developed numerical procedures are presented, and some considerations on further developments in this field are mentioned.